Credit Risk-Return Puzzle: Asian Countries Representative - Singagerda, Faurani Santi; Suryanto, Tulus; Sudjana, Jesscia Christina (Journal of Accounting and Business Education, 2017)
This Â research Â investigates Â the Â presence Â ofÂ  Credit Â Risk-Return Â Puzzle Â on Â Indonesia, Â China, Japan and Singapore, Â by analyzing Â the relationship Â betweenÂ  credit risk and stock return with the utilization of credit ratings from Moodyâs to represent credit risk. The data comprises of monthly data from January 2001 to December 2015, compiled in an unbalanced panel and then regressed with the Hausman-Taylor Â EstimatorÂ  due to the presence Â of time-invariant Â variablesÂ  such as countries Â and country classifications within the dataset.The results from this research show that Credit Risk-Return Puzzle exists in both developed andÂ  developing Â market for long-term Â credit ratings, proven by the negativeÂ  relationship Â betweenÂ  stock return and credit ratings. On the other hand Credit Risk-Return Puzzle does not exist in the case of credit rating changes in terms of direction but do show some signs of existence through difference in magnitude, Â asÂ  different Â reasons Â underlying Â credit Â rating Â changes Â such Â asÂ  leverage Â changes Â can change the direction of stock price movement.Â Keywords: credit risk-return puzzle, credit rating announcements, credit risk, impact of rating changes, decoupling-recoupling hypothesis